Legal Analysis of Trademark Protection Against Product Counterfeiting in Indonesia - Cucu Robiatul Adawiah; Nila Syapitri Hsb; Revameila Susanti; Ikhwan Aulia Fatahillah (Anthroposia: Journal of Social and Human Development, 2026)
Legal protection of trademarks constitutes an essential aspect of the Intellectual Property Rights (IPR) regime, aimed at ensuring legal certainty, protecting business actors, and preventing unfair competition. However, in practice, product counterfeiting using trademarks without authorization either identical or substantially similar remains prevalent, causing significant losses to trademark owners and consumers. This study aims to analyze the legal regulation of trademarks in Indonesia, the forms of legal protection against trademark counterfeiting, and the effectiveness of its law enforcement. The research employs a normative juridical method with statutory and conceptual approaches. The results indicate that trademark regulation in Indonesia is comprehensively governed under Law Number 20 of 2016 concerning Trademarks and Geographical Indications, which provides both preventive and repressive legal protection. Preventive protection is implemented through the trademark registration system, while repressive protection is carried out through civil, criminal, and administrative sanctions. Nevertheless, the effectiveness of law enforcement still faces several challenges, including low public legal awareness, weak supervision, and technological developments that facilitate the distribution of counterfeit goods. Therefore, it is necessary to optimize law enforcement and enhance legal awareness to achieve effective trademark protection in Indonesia.